PENGARUH EARNINGS MANAGEMENT DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DIMODERASI SALES GROWTH - Ahmad Rifaldi (2022)
This study aims to examine the effect of earnings management and capital intensity on tax avoidance with sales growth as a moderating variable. This study uses a sample, namely manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used in this study, namely the purposive sampling method with the acquisition of a sampling of 123 samples. The data analysis technique used in this study uses multiple regression analysis and moderation regression analysis with results showing that earnings management and capital intensity have a significant effect on tax avoidance. Meanwhile, sales growth cannot moderate earnings management and capital intensity on tax avoidance.